Gain recovery dynamics in active type-II semiconductor heterostructures - Meier, Torsten; Schäfer, F.; Stein, M.; Lorenz, J.; Dobener, F.; Ngo, C.; Steiner, J. T.; Fuchs, C.; Stolz, W.; Volz, K.; Hader, J.; Moloney, J.V.; et al. (Applied Physics Letters)

Temporal sorting of optical multi-wave-mixing processes in semiconductor quantum dots - Meier, Torsten; Grisard, S.; Trifonov, A.V.; Rose, Hendrik; Reichhardt, R.; Reichelt, Matthias; Schneider, C.; Kamp, M.; Höfling, S.; Bayer, M.; Akimov, I.A (arxiv:2302.02480)

Entanglement of particles versus entanglement of fields: Independent quantum resources - Sperling, Jan; Agudelo, Elizabeth (Physical Review A)

Detector entanglement: Quasidistributions for Bell-state measurements - Sperling, Jan; Gianani, Ilaria; Barbieri, Marco; Agudelo, Elizabeth (Physical Review A)

Tracking Quantum Coherence in Polariton Condensates with Time-Resolved Tomography - Lüders, Carolin; Pukrop, Matthias; Barkhausen, Franziska; Rozas, Elena; Schneider, Christian; Höfling, Sven; Sperling, Jan; Schumacher, Stefan; Aßmann, Marc (Physical Review Letters)
Keywords: General Physics and Astronomy

Experimentelle Kompetenz Physikstudierender. Entwicklung und erste Erprobung eines performanzorientierten Kompetenzstrukturmodells unter Nutzung qualitativer Methoden - Bauer, Anna Brigitte

Compact Metasurface-Based Optical Pulse-Shaping Device - Geromel, René; Georgi, Philip; Protte, Maximilian; Lei, Shiwei; Bartley, Tim; Huang, Lingling; Zentgraf, Thomas (Nano Letters)
Dispersion is present in every optical setup and is often an undesired effect, especially in nonlinear-optical experiments where ultrashort laser pulses are needed. Typically, bulky pulse compressors consisting of gratings or prisms are used to address this issue by precompensating the dispersion of the optical components. However, these devices are only able to compensate for a part of the dispersion (second-order dispersion). Here, we present a compact pulse-shaping device that uses plasmonic metasurfaces to apply an arbitrarily designed spectral phase delay allowing for a full dispersion control. Furthermore, with specific phase encodings, this device can be used to temporally reshape the incident laser pulses into more complex pulse forms such as a double pulse. We verify the performance of our device by using an SHG-FROG measurement setup together with a retrieval algorithm to extract the dispersion that our device applies to an incident laser pulse.
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Aus Erklärvideos lernen - Kulgemeyer, Christoph; Sterzing, Fabian; Hörnlein, Madeleine (Digital Physik unterrichten. Grundlagen, Impulse, Perspektiven)

Förderung von digitalisierungsbezogenen Kompetenzen von angehenden Physiklehrkräften mit dem SQD-Modell im Projekt DiKoLeP - Weiler, David; Burde, Jan-Philipp; Große-Heilmann, Rike Isabel; Lachner, Andreas; Riese, Josef; Schubatzky, Thomas (Lehr-Lern-Labore und Digitalisierung)

Von der "Shallowing Hypothese" zur "Illusion of Understanding" -wie wirken Erklärvideos und Lehrbuchtexte auf Wissen und Verstehensillusion? - Kulgemeyer, Christoph; Sterzing, Fabian; Hörnlein, Madeleine

"Aus Erklärvideos lernt man nur oberflächlich" - oder erwirbt man auch Konzeptwissen? - Hörnlein, Madeleine; Kulgemeyer, Christoph

A Pulsed Lidar System With Ultimate Quantum Range Accuracy - Kruse, Stephan; Serino, Laura; Folge, Patrick Fabian; Echeverria Oviedo, Dana; Bhattacharjee, Abhinandan; Stefszky, Michael; Scheytt, J. Christoph; Brecht, Benjamin; Silberhorn, Christine (IEEE Photonics Technology Letters)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Forschungsdatenmanagement erleichtern durch relationale Datenbanken: Ein Datenmodell für naturwissenschaftsdidaktische Forschung - Buschütter, David; Zeller, Jannis; Oltmanns, Stefan; Borowski, Andreas; Kulgemeyer, Christoph; Riese, Josef; Vogelsang, Christoph (Lernen, Lehren und Forschen in einer digital geprägten Welt Gesellschaft für Didaktik der Chemie und Physik Jahrestagung in Aachen 2022)

Entwicklung von Schülervorstellungen zu NOS & NOSI im Physikunterricht - Zwick, Linda; Webersen, Yvonne; Wodzinski, Rita (Lernen, Lehren und Forschen in einer digital geprägten Welt Gesellschaft für Didaktik der Chemie und Physik Jahrestagung in Aachen 2022)

Entwicklung und Evaluation einer NdN-Unterrichtsreihe zur Unterstützung von Lernpfaden - Webersen, Yvonne (Lernen, Lehren und Forschen in einer digital geprägten Welt Gesellschaft für Didaktik der Chemie und Physik Jahrestagung in Aachen 2022)

How authenticity impacts validity: Developing a model of teacher education assessment and exploring the effects of the digitisation of assessment methods Über Validität und Authentizität: Effekte des Transfers von Testinstrumenten in ein digitales Format auf die erhobenen Aspekte der professionellen Handlungskompetenz - Kulgemeyer, Christoph; Riese, Josef; Vogelsang, Christoph; Buschhüter, David; Borowski, Andreas; Weißbach, Anna; Jordans, Melanie; Reinhold, Peter; Schecker, Horst (Zeitschrift für Erziehungswissenschaft)
Abstract Based on a literature review of studies on teachers’ professional competence and related assessment tools, this paper introduces a model of teacher education assessment. It is influenced by Miller’s (1990) framework of assessment in medical education and includes, among other aspects, performance assessments. This model is used to understand the potential effects of transferring assessment tools into a digital format with assessment feedback. Five examples for such a transfer will be discussed: three methods for various aspects of communication, a test for pedagogical content knowledge, and a test for content knowledge. All five are established instruments well-described in terms of validity. All five have recently been transferred into a digital format. The analysis of this transfer also reveals a potentially harmful effect of digital assessment. The closer an assessment instrument is to assessing action-related parts of professional competence, the more authenticity is required; however, digitisation tends to decrease this authenticity. This suggests that an increasing number of digital assessment tools in teacher education might result in an even more dominant focus on knowledge tests, ignoring other parts of professional competence. This article highlights the role of authenticity in validity and discusses the most suitable assessment format to address various parts of professional competence. It ends by highlighting the lessons learned from the transfer of assessment instruments into a digital format that other academic disciplines might find interesting.
Keywords: Education

Erwerb und Messung fachdidaktischen Wissens zum Einsatz digitaler Medien - Große-Heilmann, Rike Isabel; Burde, Jan-Philipp; Riese, Josef; Schubatzky, Thomas; Weiler, David (Lernen, Lehren und Forschen in einer digital geprägten Welt Gesellschaft für Didaktik der Chemie und Physik Jahrestagung in Aachen 2022)

Unterrichtsplanung mit sinnvoller Einbettung digitaler Medien im PU - Jordans, Melanie; Riese, Josef (Lernen, Lehren und Forschen in einer digital geprägten Welt Gesellschaft für Didaktik der Chemie und Physik Jahrestagung in Aachen 2022)

Datenbasierte Fähigkeitsprofile im Physikdidaktischen Wissen - Zeller, Jannis; Riese, Josef (Lernen, Lehren und Forschen in einer digital geprägten Welt Gesellschaft für Didaktik der Chemie und Physik Jahrestagung in Aachen 2022)

Theoretical analysis of four-wave mixing on semiconductor quantum dot ensembles with quantum light - Rose, Hendrik; Grisard, S.; Trifonov, A. V.; Reichhardt, R.; Reichelt, Matthias; Bayer, M.; Akimov, I. A.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XXVII)
The nonlinear optical response of an ensemble of semiconductor quantum dots is analyzed by wave-mixing processes, where we focus on four-wave mixing with two incident pulses. Wave-mixing experiments are often described with semiclassical models, where the light is modeled classically and the material quantum mechanically. Here, however, we use a fully quantized model, where the light is given by a quantum state of light. Quantum light involves more degrees of freedom than classical light as e.g., its photon statistics and quantum correlations, which is a promising resource for quantum devices, such as quantum memories. The light-matter interaction is treated with a Jaynes-Cummings type model and the quantum field is given by a single mode since the quantum dots are embedded in a microcavity. We present numerical simulations of the four-wave-mixing response of a homogeneous system for pulse sequences and find a significant dependence of the result on the photon statistics of the incident pulses. The model constitutes a problem with a large state space which arises from the frequency distribution of the transition energies of the inhomogeneously broadened quantum dot ensemble that is coupled with a quantum light mode. Here we approximate the dynamics by summing over individual quantum dot-microcavity systems. Photon echoes arising from the excitation with different quantum states of light are simulated and compared.